3D Infant Orthopedic Nasal Molding System for Improved Outcomes in Cleft Nasal Deformity. Issue 2 (June 2023) - Mejia, Martha L.; Pablo Gomez, Juan; Moon, Savannah L.; Wolfe, Erin M.; Perlyn, Chad A.; Anthony Wolfe, S.; Steinberg, Jordan P.
The cleft nasal deformity is a hallmark feature in infants with cleft lip and palate and includes deviation of the caudal septum, slumping of the ipsilateral lower lateral cartilage, and obstructed nasal breathing. Presurgical orthopedic protocols have been developed and refined over several decades now, with limited evidence supporting their long-term efficacy, particularly with respect to the nasal form. Some limitations relate to variabilities in studies and data outcome measures. We have designed a novel method of presurgical orthopedic molding using separate nasal and intraoral components. The independent nasal device, called the Rhinoplastic Appliance System, is introduced in this technique article and shown to have distinct biomechanical advantages for the unilateral and bilateral cleft nasal deformity, both presurgically before lip repair, and postsurgically for nostril maintenance. As with CAD/CAM technologies for the intraoral plate component of traditional NAMs, we believe digital preparation of RAS devices, combined with separate oral appliances, can allow for more effective and reproducible presurgical infant cleft molding with less operator dependence and family/patient burden.